From system to pedagogy: towards a nonlinear pedagogy of self-defense training in the police and the civilian domain. Issue 2 (April 2018) - Körner, Swen; Staller, Mario
Abstract Within public and academic spheres, the question of how civilians and police officers can effectively deal with violent assaults is discussed above all as a question of the "right self-defense system." In the current paper, we advocate for a change from questions of system to questions of pedagogy. Based on the paradigm of nonlinear pedagogy and the underlying theories of complex dynamic systems, we present a model of representative learning design, whose analytical and practical use is presented. We conclude with a discussion of the role of nonlinear pedagogy for the professionalization of self-defense training in the civilian and law enforcement domains.